(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
On the basis of ammonoids collected in the uppermost part of the Prezzo Limestone (Anisian), the new genus Lardaroceras and two new species L. krystyni (type species) and L. pseudohungaricum are described; a third one is left in open nomenclature. The genus Lardaroceras comprises involute and compressed ceratitids, whose subtrapezoidal whorl section is characterized by an evident periumbilical margin and a rounded ventral keel. The ornamentation is made of umbilical and lateroventral nodes, to which sometimes lateral nodes are added, and of lightly proverse and sinuous, primary, intercalatory and bifurcate ribs. The very distinctive suture line is subammonitic. The two species, L. krystyni and L. pseadohungaricam, differ mainly in the ornamentation and in the adult body chember: the former has umbilical and lareroventral nodes and its ornamentation fades on the adult body chamber, the latter has also lateral nodes and its ornamentation strengthens in the latest stage of growth. Because of the suture line the genus is attributed to the subfamily Beyrichitinae. The stratigraphic significance of the new genus is also discused.